One piece. Skypiea vol. 26 Skypiea - Oda, Eiichiro, 1975- (San Francisco, CA : VIZ Media, LLC, 2014)
The Straw Hats must cut their visit to Alabasta short when Monkey D. Luffy--who has the power to stretch like rubber--attracts too much attention, but the crew must really make haste after word reaches Mr. Zero--a.k.a. Sir Crocodile--that Luffy is still alive, as he orders his minions to eliminate his enemy once and for all.
"First published in Japan in 1997 by Shueisha Inc, Tokyo"--Page facing t.p.
"Parental advisory. One Piece is rated T for teen and is recommended for ages 13 and up. This v. contains fantasy violence and tobacco usage"--Page facing t.p.
"This book reads from right to left"--Back cover.
"This v. contains material that was originally published in English in Shonen Jump #62-65"--Page facing t.p.
Translated from the Japanese.
5-8.
Keywords: Pirates -- Comic books, strips, etc. -- Fiction; Treasure troves -- Comic books, strips, etc. -- Fiction; Buried treasure -- Comic books, strips, etc. -- Fiction; Manga; Pirates -- Comic books, strips, etc. -- Fiction; Action and adventure comics; Graphic novels